TRIP-assisted compressive ductility in Ti-rich Ti60Mo10V10Cr10Zr10 refractory medium-entropy alloy. (November 2021) - Lee, Seongi; Choi, Gwanghyo; Lee, Kwangmin
Abstract: Compositional tuned non-equiatomic refractory high-entropy alloys are coveted materials as they achieve considerable plasticity through transformation-induced plasticity (TRIP) behavior. In this study, a novel Ti-rich Ti60 Mo10 V10 Cr10 Zr10 refractory medium-entropy alloy (RMEA) was designed using FactSage. The plastic deformation of the alloy produced using vacuum arc remelting was investigated through a room-temperature compression test at different strain rates. A high strain-hardening rate and an m -value of 0.031 were observed in the Ti-rich Ti60 Mo10 V10 Cr10 Zr10 RMEA. The dimple structures formed in BCC phases and TRIP-assisted deformation attribute to the strength and ductility trade-off in Ti-rich Ti60 Mo10 V10 Cr10 Zr10 RMEA. Highlights: Ti60 Mo10 V10 Cr10 Zr10 RMEA showed a single BCC1 phase High strain-hardening rate in Ti-rich Ti60 Mo10 V10 Cr10 Zr10 RMEA led to the enhanced compressive strength of the alloy. TRIP-assisted deformation attributes to the remarkable compressive strain of the Ti-rich Ti60 Mo10 V10 Cr10 Zr10 RMEA.